THE PERCEPTION OF INVESTORS TOWARDS INITIAL PUBLIC OFFERING: EVIDENCE OF NEPAL - Achut Gnawali; Ballav Niroula (Program Studi Manajemen Pemerintahan dan Keuangan Daerah Fakultas Ekonomi dan Bisnis Universitas Jambi, 2021)
The main aim of this study is to examine the perception of investors towards initial public offering (IPO), to analyze the relationship between different factors (quality management, company goodwill, company performance, company sector, and market information) and investment decision to examine the factors that impact in IPO to making an investment decision. This research used primary data. The data was collected from 290 respondents which were related to five different brokerage firms at Kathmandu district. The inferential analysis was preferred in SPSS by using statistical tools such as correlation and regression analysis to analyze the relationship between variables and the impact of different factors on investment decisions. The study revealed that quality management, company goodwill, company performance, company sector, and market information are the highly considerable factors before making investment decisions in IPO.